Cardiovascular medication adherence among patients with cardiac disease: a systematic review. (28th July 2016) - Al‐Ganmi, Ali Hussein; Perry, Lin; Gholizadeh, Leila; Alotaibi, Abdulellah Modhi
Abstract: Aims: The aim of this study was to critically appraise and synthesize the best available evidence on the effectiveness of interventions suitable for delivery by nurses, designed to enhance cardiac patients' adherence to their prescribed medications. Background: Cardiac medications have statistically significant health benefits for patients with heart disease, but patients' adherence to prescribed medications remains suboptimal. Design: A systematic quantitative review of intervention effects. Data Sources: We conducted systematic searches for English‐language, peer‐reviewed randomized controlled trial publications via Medline, EMBASE, CINAHL, the Cochrane Library, ProQuest, Web of Science and Google Scholar published between January 2004–December 2014. Review methods: According to pre‐determined inclusion and exclusion criteria, eligible studies were identified and data extracted using a predefined form. Of 1962 identified papers; 14 studies met the study inclusion criteria, were assessed for risk of bias using the Cochrane Collaboration tool; and included in the review. Results: Study findings were presented descriptively; due to the heterogeneity of studies meta‐analysis was not possible. Included papers described interventions categorized as: (1) multifaceted; and (2) behavioural and educational, comprising: (a) text message and mail message; (b) telephone calls; (c) motivational interviewing and (d) nurse‐led counselling and education. Conclusions: Substantial heterogeneity limited the robustness of conclusions, but this review indicated that motivational interviewing, education and phone or text messaging appeared promising as means to enhance cardiac medication adherence. Future research should integrate multifaceted interventions that target individual behaviour change to enhance adherence to cardiovascular medications, to build on the beneficial outcomes indicated by this review.